Association between high sensitivity C-Reactive protein and prevalence of asymptomatic carotid artery stenosis. (March 2016) - Huang, Xiaoya; Wang, Anxin; Liu, Xiaoxue; Chen, Shengyun; Zhu, Ying; Liu, Yanfang; Huang, Keyu; Wu, Jianwei; Chen, Shouhua; Wu, Shouling; Zhao, Xingquan
Abstract: Introduction: Inflammation plays a key role in the pathophysiology of atherosclerosis. Little is known about the association between high sensitivity C-reactive protein (hs-CRP) especially long-term hs-CRP and asymptomatic carotid artery stenosis (ACAS) in healthy Chinese adults. The aim of this study was to assess the relationship between hs-CRP levels and the prevalence of ACAS in a Chinese community-based cohort. Methods: A sample of 5349 participants aged ≥40 years (40.36% women) were enrolled in this study, all without preexisting stroke. Ultrasonography of the bilateral carotid arteries was performed for the evaluation of carotid stenosis. Participants were stratified into three groups according to hs-CRP levels. We used both baseline (hs-CRP levels analyzed during 2010) and average hs-CRP values for the last four years (the average of hs-CRP levels analyzed at the year of 2006, 2008 and 2010) in the analysis. Multivariable logistic regression models were used to analyze the association between hs-CRP levels and ACAS. Results: A total of 356 (6.66%) subjects showed evidence of ACAS. Multivariate analysis showed that both baseline and average hs-CRP values for the last four years were independent indicators for the presence of ACAS (P for trend = 0.007, 0.001, respectively). Stratified by age and sex, higher baseline hs-CRP levels were associated with ACAS in old adults (≥60 y) (multivariate-adjusted, odds ratio [OR] = 1.03, 95% confidence interval [CI]: 1.01–1.05) and male (multivariate-adjusted, OR = 1.03, 95%CI: 1.01–1.05), but not in middle-aged adults (40–59 y) and female. Similarly, higher average hs-CRP values for the last four years were associated with ACAS in old adults and male, but not in middle-aged adults and female. Conclusion: Both baseline and chronic elevation of serum hs-CRP were associated with ACAS, especially in older or male adults. hs-CRP might be used as a useful marker and a potential therapeutic target for carotid atherosclerosis. Highlights: Baseline hs-CRP values were independent indicators for ACAS. Significant interactions were observed between age and sex in relation to ACAS. Elevated baseline hs-CRP values increased ACAS in old adults and male. The results of average hs-CRP values were consisted with baseline hs-CRP.